Improved Governance of Business Financial Reporting in MSMEs CV Gayatex Indo - Sari, Gentrin Mudiah; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2023)
In addition, it is also to increase knowledge and skills in managing CV finances. Gayatex Indo complies with exist-ing guidelines. The method used in this community service activity is through the lesson study method using three stages, namely planning, implementation and reflection. The implementation method is manifested in mentoring, consultation and discussion activities. The result of this community service activity is to improve the knowledge and skills of partners in this case CV.Gayatex Indo in compiling and managing its business financial statements to be more effective and efficient so that it can help im-prove business financial performance and strengthen busi-ness position in the global market. By implementing good financial governance, it will make it easier for MSMEs to develop their business. For this reason, the importance of implementing financial statements is applied properly and in accordance with established regulations.